Slower Long‐Term Coastal Warming Drives Dampened Trends in Coastal Marine Heatwave Exposure. Issue 11 (15th November 2021) - Marin, Maxime; Bindoff, Nathaniel L.; Feng, Ming; Phillips, Helen E.
Abstract: Long‐term temperature changes drive coastal Marine Heatwave (MHW) trends globally. Here, we provide a more comprehensive global analysis of cross‐shore gradients of MHW and Sea Surface Temperatures (SST) changes using an ensemble of three satellite SST products during recent decades. Our analysis reveals depressed onshore SST trends in more than 2/3 of coastal pixels, including both eastern and western boundary current systems. These were well correlated with depressed trends of MHW exposure and severity, ranging from a −2 to −10 decrease in MHW days per decade and from a −2.5°C to −15°C.days per decade decrease in cumulative intensity. Results were consistent across all satellite products, indicating that these cross‐shore gradients are a robust feature of observations. ERA reanalysis data show that neither air‐sea heat fluxes nor wind driven upwelling were found to be consistent drivers. Global ocean circulation models (OFAM3 and ACCESS‐OM2) have limited ability to simulate the depressed onshore trends. A heat budget analysis performed in the Chilean coast region, where models agree with observations, showed that the gradient of temperature change was controlled by an onshore increase of longwave radiative cooling, despite an increase in upwelling. This highlights the complexity of small‐scale coastal ocean‐atmosphere feedbacks, which coarser resolution climate models do not resolve. Here, we show that global coastal regions may act as thermal refugia for marine ecosystems from aspects of climate change and pulsative (MHW) changes. Contrary to the literature, our results suggest that driving mechanisms are region dependant, stressing the necessity to improve climate models resolution. Plain Language Summary: We analyze differences of the long‐term change of Marine Heatwave (MHW) and Sea Surface Temperatures (SST) between coastal and offshore regions, using three different satellite SST products. We found that, in 2/3 of cases, the rate of change of SST in coastal regions was lower than offshore. As most regions have experienced recent warming, this means that the warming was slower near the coast. This phenomenon was observed along most coastlines. Slower rates of SST change were well correlated with slower rates of MHW change. Our results were observed in all three SST products, indicating that this phenomenon is not due to errors associated with satellite measurements. Using reconstructed atmospheric data, we show that neither air‐sea exchanges nor wind driven upwelling could explain the smaller coastal change consistently. Global ocean circulation models (OFAM3 and ACCESS‐OM2) were not able to simulate this signal in every region. However, results from a heat budget analysis performed in regions of agreement highlighted the complexity of ocean‐atmosphere exchanges happening on a small scale, that coarse resolution climate models do not resolve. Here, we demonstrate that global coastal regions may act as a refugia for marine ecosystems under increasing threat from rising temperatures. Key Points: Slower onshore Sea Surface Temperatures (SST) warming trends drive depressed Marine Heatwave (MHW) trends relative to offshore along most global coastlines Results were consistent across all observations but models show a limited ability to simulate this signal A heat budget analysis of a case study region highlights the complexity of ocean‐atmosphere feedback often not resolved in climate models